Peningkatan Produktivitas Melalui Pengembangan Aplikasi Pengelolaan Keuangan pada Sade Arch Design dan Building - Dwi Narullia; Ria Zulkha Ermayda; Dhika Maha Putri; Sheila Febriani Putri; Nurman Fadhilah (Universitas Muhammadiyah Malang, 2024)
Purpose – This article presents a community service initiative focused on enhancing financial management at SADE Arch Design & Building Micro, Small, and Medium Enterprises (MSMEs) through the implementation of a unique financial management application. Design/methodology/approach – The service activities spanned four stages: conducting Focus Group Discussions, developing the application, introducing it to partners, and evaluating its usage. The approach involved delivering both the developed financial management application and comprehensive training to the SADE Arch Design & Building MSMEs. Findings – The result of this service activity is the establishment of a financial management application equipped with various features that help SADE Arch Design & Building in preparing financial reports more easily and improve their financial management skills. In addition, this activity also helps SADE Arch Design & Building in improving financial understanding, practical application, measuring performance, strategic planning, and legal compliance. Originality/value – This service activity has a positive impact on improving the financial literacy of MSMEs, especially SADE Arch Design & Building, through the development of Microsoft Excel-based financial management applications. With the application of technology and innovative approaches, this activity has succeeded in increasing the efficiency and accuracy of financial reports, providing concrete solutions to traditional constraints in MSME financial management. is a solution to overcome the problems faced by MSMEs in Malang City.